Strategi Pengelolaan Usaha Berbasis Digital Untuk Meningkatkan Efisiensi Operasional - Karona Cahya Susena; Nenden Restu Hidayah (Jurnal Dehasen Mengabdi, 2026)
Limited manual business management remains a major obstacle for micro, small, and medium enterprises (MSMEs) in improving operational efficiency. This community service aims to enhance operational efficiency through digital-based business management strategies. The method used includes training and assistance in using digital applications for financial recording and inventory management. Evaluation was conducted using pre-test and post-test as well as direct observation. The results show an increase in operational efficiency by 55%, indicated by faster transaction recording and more accurate inventory management. Additionally, participants’ understanding of digital technology increased by 60%. This program positively impacts business performance and data-driven decision-making. It is recommended to provide continuous assistance and digital infrastructure support.